1970
DOI: 10.1128/iai.2.3.237-243.1970
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Components of Cell Walls of Brucella abortus Strains of Low and High Virulence

Abstract: Amino acid, carbohydrate, and lipid components of cell walls of Brucella abortus strain 19A (low virulence) and strain 2308 (high virulence) were compared by thin layer chromatography (TLC) and by use of an amino acid analyzer. A total of 15 amino acids were detected by both chromatographic methods. Each amino acid was present in greater amounts in strain 2308 than in strain 19A when equal amounts of hydrolysates of cell wall and endotoxin-containing preparations were analyzed. A component with the same R, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…There are conflicting reports on the presence of heptose in brucella S-LPS. Although some investigators (26)(27)(28)41) reported heptose, Hurvell and Lindberg (19) did not detect it on analysis by GLC of S-LPS (f5) extracted by the Redfearn method. We also could not detect this sugar in the S-LPS and R-LPS of B. abortus.…”
Section: Sds-page Sds-page Patterns Of F5 F5pmentioning
confidence: 99%
“…There are conflicting reports on the presence of heptose in brucella S-LPS. Although some investigators (26)(27)(28)41) reported heptose, Hurvell and Lindberg (19) did not detect it on analysis by GLC of S-LPS (f5) extracted by the Redfearn method. We also could not detect this sugar in the S-LPS and R-LPS of B. abortus.…”
Section: Sds-page Sds-page Patterns Of F5 F5pmentioning
confidence: 99%
“…The currently approved vaccine strain, S19, has several disadvantages, including human infectivity and virulence, and a low level of persistently infected, vaccinated cattle (10,15,45). The search for improved vaccines or diagnostic reagents capable of distinguishing field strain infections from S19-vaccinated or persistently infected animals comprises most current Brucella research (9,12,28,46,50,51,64,65).…”
mentioning
confidence: 99%
“…Although quantitative antigenic differences are recognized among B. abortus biotypes, qualitative differences may be more closely related to virulence of these species. Several studies on the immunity invoked by challenge of animals with Brucella antigens suggest that a substance, absent in attenuated organisms, is responsible for preventing destruction of virulent strains during phagocytosis (12,17,23). Thus, the demonstration of antigens or components common to virulent biotypes that are not apparent in attenuated or avirulent strains could add to our Photographic and diagrammatic reproductions ofpolyacrylamide gel isoelectric focusing patterns of soluble antigens derived from four strains of B. abortus in a pHgradient of 3.0 to 10.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, agglutination reactions indicate that quantitative differences in the distribution of two major Brucella agglutinogens (A and M) exist among the different biotypes (19,28). Numerous attempts have been made to demonstrate in virulent strains of brucellae the presence of antigens that are not present in attenuated or avirulent strains (1,8,12,15,17,20,23). Results of such studies suggest that basic studies concerning antigenic differences existing between virulent and attenuated or avirulent strains of different biotypes might contribute to a better understanding of factors related to virulence and/or immunogenicity of Brucella species.…”
mentioning
confidence: 99%